THE CONCEPTUAL PROBLEM OF PROBLEM-BASED LEARNING AS A LEARNING METHOD AND AS A STRATEGY - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2013)
The article presents theoretical insights of problem-based learning in order to find out the borderline between the problem-based learning method and the problem-based study strategy. Therefore, the article deals with the similarities and peculiarities of both concepts. It presents experts’ opinion (nine Georgian and Ukrainian experts, university professors participating in the TEMPUS project) on the subject under discussion as well. The theoretical part focuses on the philosophy of the problem-based study strategy the principles of which, according to T. Barret (2005), correspond to three methodological approaches: cognitivism (the active mental process leading to the acquisition of existing knowledge and its connection with new knowledge, the establishment of links between them and the development of new as well as related concepts) (H. Schmidt, 2004), social constructivism (knowledge constructed with the tutor and the group, situations are created, etc.), and postmodernism (knowledge is variable, modern thinking is dangerous for a sleeping mediocre). Both the programme design and the other necessary elements of this strategy (assessment, seminars) should correspond to the philosophy of the problem-based learning strategy. Summarizing the theoretical insights and the experts’ opinion, it could be stated that: – the problem-based learning method and study strategy are student-oriented and reflect students’ centrist position. Depending on the authors’ approach, it can emphasize either the study process or its outcome. However, in any case they are coherent with both the study process and its outcomes; – according to theoretical insights and experts’ point of view, the problem-based learning as a method is more associated with techniques or technologies applied in the study process to achieve certain didactic goals, whereas as a study strategy it is related to the whole programme which is constructed following a certain methodological approach with the focus on relationships between theory and practice in the professional filed; – problem-based learning as a method and as a study strategy are seen as a potential of students’ motivation for learning, search for harmony between theory and practice, preparation for vocational activities and real life. Experts believe they are relevant to students’ problem-solving and independent learning. This complies with theoretical insights.